Fair remuneration of workers in micro and small enterprises in Job Creation Act - Prayogo Pranowo; Tanudjaja Tanudjaja; Nynda Fatmawati Octarina (Jurnal Cakrawala Hukum, 2022)
Labor Protection is the ideal and purpose of the existence of labor law to provide legal protection in the omnibus law (Job Creation Act), which accommodates the interests of workers but also accommodates the ease of doing business in micro and small firms in the form of wages as seen in Article 90 B. the existing problems regarding the legal ratio of labor law in Indonesia based on the Job Creation Act and what are the forms of legal protection for workers in micro and small businesses based on the legislation?, the purpose of this study is to find out and analyze the ratio of labor law legislation in Indonesia. Indonesia is based on the Job Creation Act to find and explore forms of legal protection for workers in micro and small businesses. At the same time, the benefits of this research are divided into two, namely, theoretically, to provide a legal ratio to the wages of micro-enterprise workers. And small, while in practice, it is to provide legal protection for workers in Micro and Small businesses. The employment agreement is also a form of agreement regulated in the Manpower Act and the Law on Job Creation as an alternative to protecting workers' rights with the principle of proportionality which aims to increase workers’ bargaining power.How to cite item: Pranowo, P., Tanudjaja, T., Octarina, N. (2022). Fair remuneration of workers in micro and small enterprises in Job Creation Act. Jurnal Cakrawala Hukum, 13(2), 175-183. DOI:https://doi.org/10.26905/idjch.v13i2.5625.